( | 2 | x | − | 3 | ) | ÷ | 5 | = | 2 | ÷ | 3 | × | x | − | 2 |
Left side of the equation = | 2 | x | × | 1 5 | − | 3 | × | 1 5 |
= | 2 5 | x | − | 3 5 |
2 5 | x | − | 3 5 | = | 2 | ÷ | 3 | × | x | − | 2 |
Right side of the equation = | 2 3 | x | − | 2 |
2 5 | x | − | 3 5 | = | 2 3 | x | − | 2 |
2 5 | x | − | 2 3 | x | = | - | 2 | + | 3 5 |
- | 4 15 | x | = | - | 2 | + | 3 5 |
- | 4 15 | x | = | - | 7 5 |
7 5 | = | 4 15 | x |
4 15 | x | = | 7 5 |
x | = | 7 5 | ÷ | 4 15 |
= | 7 5 | × | 15 4 |
= | 7 | × | 3 4 |
x | = | 21 4 |
x | = | 5.25 |